Rancang Bangun Perpustakaan Digital Menggunakan Framework Codeigniter Pada STMIK Primakara - I Wayan Darma Yasa; I Putu Satwika; Eka Grana Aristyana Dewi (Primakara University, 2020)
Digital Library is a library that utilizes information technology to manage library collections or any library activities. Library digitization is a must for every tertiary institution because this is explained in Article 24 Paragraph (3) of Law Number 43 of 2007. In addition, digital libraries are also needed when tertiary institutions carry out university accreditation. However, at STMIK Primakara, the existing digital library system has not been able to fulfill all data such as visit statistics required at the time of accreditation. To overcome these problems, then built a system that can support it. This study uses the Personal Extreme Programming (PXP) method and uses the CodeIgniter Framework as a system actor and in testing system effectiveness using the McLean and DeLone methods. This research succeeded in building and implementing a digital library system that had been designed. From the results of the system effectiveness test carried out by distributing questionnaires to STMIK Primakara students, it can be said that the system that has been built gets pretty good results on almost every variable to test its effectiveness.